Análise de procedimentos de gestão do comitê de bacia hidrográfica do Rio São José dos Dourados para implementação da política de recursos hídricos no Estado de São Paulo - Azevedo, Fabiana Zanqueta de (2009)
The principal aim of this research was to analyze the management of the Hydrographical Basin Committee (HBC) in order to implement the Water Resources Policy (HRP) in the State of São Paulo, establishing relations among the main problems, the indicated procedures to resolve them, and the management of the HBC-SJD (Hydrographical Basin Committee of the River São José dos Dourados). The research started with the interest in knowing whether the Hydrographical Basin Committee would be fulfilling completely the objectives of the Management of Hydric Resources Integrated System (MHRIG) or not, in the quality of a consultive and deliberative organ at the regional level, for the execution of the Hydric Resources Policy in the State of São Paulo. The study object was the Hydric Resources Management Unity of the Basin of the River São José dos Dourados, taking into consideration the financial resources application from the Hydric Resources State Fund (HRSF) in the period of 2004/2008. After identifying the problems we considered their priorities from a public consult, and subsequently raised the criteria to the hierarchization of the prioritized procedures during the period being studied. We adopt the neoclassical theory of management in order to investigate both the Hydric Resources Policy and the HBC-SJD management cycle. From the examination of the main problems, of the prioritized procedures, of the chosen criteria to the hierarchization and of the management functions performed by the Committee we could verify the hypotheses of the research and thus contribute to the improvement and to the reformulation of the Policy in the region. Though the reports on The Situation of the Hydric Resources of the Hydrographical Basin and on the Plans of Hydrographical Basins are reference documents to the management, it is essential that they play a role of supervision and that they are continuously brought up-to-date, enabling the analysis of the current situation taking into account the performed procedures, supporting the planning, building settings and checking the obtained results. The recommendations and proposals presented refer to the requirement of supervision and systematic review of the adopted procedures, aiming an efficacious and efficient management of the HBCs in other hydrographical regions.